Right-Sided Dysplasia in Inflammatory Bowel Disease Is Not Associated with Conventional Risk Factors for Neoplasia - Sumona Bhattacharya; William Beaty; Adam S. Faye; Jordan E. Axelrad (Gastroenterology Insights, 2025)
Introduction: In the general population, right I-sided dysplasia presents a higher risk for colorectal cancer (CRC) and metachronous dysplasia compared to left (L)-sided dysplasia. Given that patients with inflammatory bowel disease (IBD) are at higher risk for dysplasia than the general population, we sought to assess the risk factors as well as the differences in outcomes between patients with R-sided, L-sided, and both R- and L-sided dysplasia. Methods: A retrospective chart review was performed on patients at NYU Langone Health who had evidence of dysplasia on a colonoscopy between 2011 and 2021. Demographics and pertinent medical history were compiled. Cohorts were based on the dysplasia location (R-sided, L-sided, or R- and L-sided) and the IBD-related outcomes were analyzed. Results: A total of 71 patients had colonic dysplasia. The mean age was 54 years old (SD ± 17). The majority were male (72%), white (69%), and non-Hispanic (94%). A total of 76% had ulcerative colitis (UC) and 24% had Crohn’s disease (CD). Of all dysplastic lesions, 57 (80%) patients had unifocal disease and the remainder had multifocal disease. A total of 39 (55%) patients had R-sided dysplasia, 24 (34%) had L-sided dysplasia, and 8 (11%) had both R- and L-sided dysplasia. Patients with UC were more likely to have L-sided dysplasia (92% vs. 8% in CD; p = 0.04). Pseudopolyps were more likely associated with R- and L-sided dysplasia (38% in R- and L-sided dysplasia, 10% in R-sided dysplasia, and 4% in L-sided dysplasia; p = 0.03). Conclusions: Patients with UC had a higher risk for L-sided colonic dysplasia compared to patients with CD; however, there were no differences in the progression of dysplasia between those who had R-sided and those who had L-sided dysplasia. Larger studies are needed to assess the risk factors and outcomes related to the laterality of dysplasia and further validate these findings among patients with IBD.